Epidemiological aspects of interpersonal and self-harm violence in Paiçandu-PR, in the period from 2013 to 2023 (Research, Society and Development, 2025)
Objective: To analyze the epidemiological profile of reports of interpersonal and self-inflicted violence in the region of Paiçandu - PR between 2013 and 2023. Methods: The quantitative and descriptive study used data from the National System of Injuries and Notifications (SINAN) to obtain epidemiological data and structure the research. Results: female adults, white race/color, age range between 19 and 44 years, complete high school were the main victims. There were 979 reported cases, of which 348 were self-inflicted injuries. Of the total violence data analyzed, 396 cases were caused by family members, specifically mother (14%) and spouse (13%), with the highest registration rate. The highest incidence of cases was in 2021 with 195 reports, corresponding to 20% of the reports in the period analyzed. Regarding the evolution of cases of violence, 928 records were blank, making it impossible to analyze the outcome of the events due to the lack of records. It is concluded that interpersonal violence and self-harm are public health problems. It is important to train health teams to correctly record notifications, since without this epidemiological data, prevention and intervention strategies for violence are compromised.